HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN KEJADIAN INSOMNIA PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS ISLAM AL-AZHAR ANGKATAN 2021 - Danang Nur Adiwibawa; Tri Aris Munandar; Siti Ruqayyah; Ayu Anulus (Nusantara Hasana Journal, 2023)
Background: Due to the development of science, technology, and information, the use of social media is increasingly inseparable from society. A study conducted by the Ministry of Communication and Information Technology (Kemkominfo) in collaboration with the United Nations International Children's Emergency Fund (UNICEF) in 2014 showed the fact that social media users reached more than 82 million people and made Indonesia the 8th largest in the world as a social media user. The use of social media through gadgets will interfere with the regulation of the hormone melatonin so that it can cause insomnia for its users, including students. Objective: To determine the relationship between the use of social media and the incidence of insomnia in students of the Faculty of Medicine, Al-Azhar Islamic University batch 2021. Method: This study was an observational analytic studied, with a cross sectional design. The sample used is the students of Faculty of Medicine, Al-Azhar Islamic University batch 2021 with a total of 91 people. The insomnia assessment was carried out using the KSPBJ-IRS insomnia questionnaire and the use of social media was assessed using a measuring instrument in the form of a questionnaire adopted from Ruri Selvia's undergraduate thesis (2020). Data analysis using Chi-Squere with SPSS software version 25. Results: Analysis using Chi-Square obtained a p-value of 0.001 (p-value <0.05), which means that there is a significant relationship between the use of social media and the incidence of insomnia in students of the Faculty, of Medicine Al-Azhar Islamic University batch 2021. Conclusion: There is a relationship between the use of social media with the incidence of insomnia in students of the Faculty of Medicine, Al-Azhar Islamic University batch 2021.